KONSEP MASHLAHAH AL-AMMAH DALAM PERSPEKTIF FIQH SOSIAL KH. MA. SAHAL MAHFUDH - Arif Chasanuddin; Zahrotun Nafisah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
This research have to know mashlahah al-‘ammah of concept in the Kiai Sahal’s social fiqh perspective to encourage the presence fiqh modernity to be most productive, progressive and contectual as problem solving a umat appropriate ages. This research is library research with kualitative-descriptive method. The autor used histories-philosophy by phenomenon. In the step of analysis, the autor used content Philipp Mayring model as instrument disinterment Mashlahahal-‘Ammah by populer creation Kiai Sahal the tittle Kitab Thariqatal-usul Ala Ghoyatal-Wusul. Output this research, Kiai Sahal’s Mashlahahal-Ammah concept being efort and prevent a detriment basis to syara direction in the specific zone, not only with a determine requirement indicator, like Dharuriyah, Hajjiyah and Tahsiniyah in a external manner but also human being to have a feeling be happy in the beyond (Saadatuddarain).